Challenges and Advances in the Encapsulation of Bioactive Ingredients Using Whey Proteins - Manuel Figueiredo; Zsuzsa Sárkány; Fernando Rocha; Pedro M. Martins (Foods)
Functional foods represent an emerging trend in the food industry. Fortifying foods with bioactive ingredients results in health benefits and reduces the risk of disease. Encapsulation techniques protect sensitive ingredients from degradation due to heat, light, moisture and other factors. Among encapsulating materials, milk whey proteins are particularly attractive due to their availability, GRAS status and remarkable ligand-binding ability. Whey protein was once considered a by-product in the dairy industry but is now seen as a promising resource given its natural role as a nutrient carrier. This work reviews the encapsulation systems that employ whey proteins in the food industry. The structural features of β-lactoglobulin (β-LG), the main protein constituent of milk whey, are presented in the context of its ligand-binding properties. Different types of encapsulation systems using whey proteins are discussed, focusing on the recent advances in stable formulations of bioactives using whey protein, alone or in hybrid systems. Whey proteins are a valuable asset capable of binding sensitive bioactive compounds such as vitamins, polyphenols and antioxidants and forming stable complexes that can be formulated as nanoparticles, nanofibrils, emulsions and other micro- and nanostructures. Developing scalable, solid and stable encapsulation systems is identified as a main challenge in the field.